Nosocomial Bloodstream Infections in Brazilian Hospitals: Analysis of 2,563 Cases from a Prospective Nationwide Surveillance Study - Marra, Alexandre Rodrigues [UNIFESP] (2011)
Nosocomial bloodstream infections (nBSIs) are an important cause of morbidity and mortality. Data from a nationwide, concurrent surveillance study, Brazilian SCOPE (Surveillance and Control of Pathogens of Epidemiological Importance), were used to examine the epidemiology and microbiology of nBSIs at 16 Brazilian hospitals. in our study 2,563 patients with nBSIs were included from 12 June 2007 to 31 March 2010. Ninety-five percent of BSIs were monomicrobial. Gram-negative organisms caused 58.5% of these BSIs, Gram-positive organisms caused 35.4%, and fungi caused 6.1%. the most common pathogens (monomicrobial) were Staphylococcus aureus (14.0%), coagulase-negative staphylococci (CoNS) (12.6%), Klebsiella spp. (12.0%), and Acinetobacter spp. (11.4%). the crude mortality was 40.0%. Forty-nine percent of nBSIs occurred in the intensive-care unit (ICU). the most frequent underlying conditions were malignancy, in 622 patients (24.3%). Among the potential factors predisposing patients to BSI, central venous catheters were the most frequent (70.3%). Methicillin resistance was detected in 157 S. aureus isolates (43.7%). of the Klebsiella sp. isolates, 54.9% were resistant to third-generation cephalosporins. of the Acinetobacter spp. and Pseudomonas aeruginosa isolates, 55.9% and 36.8%, respectively, were resistant to imipenem. in our multicenter study, we found high crude mortality and a high proportion of nBSIs due to antibiotic-resistant organisms.